Attitudes and Supports on Pregnant Women’s Intention in HIV Testing and Breastfeeding Decision - Nina Mardiana; Evy Nurachma; Rita Kirana; Yona Polin (Indonesian Journal of Multidisciplinary Science, 2023)
HIV/AIDS is a disease caused by a virus that attacks the human body's immunity. It continues to increase from year to year and can transmit the disease from mother to child. More than 9,000 pregnant women with HIV positive status every year and 30% of them give birth to HIV positive babies. The purpose of this study analyzed the attitude, support (husband, health workers, friends) towards the intention of pregnant women to do HIV testing and the decision to breastfeed in the city of Balikpapan. This study used a survey method with a cross-sectional study design. The sampling was applied to 124 people of Puskesmas. Descriptive and analytical data analysis with frequency distribution and PLS (Partial Least Square) were used. The results showed that the youngest pregnant women were 17 years old and the oldest 41 years old, most pregnant women received good support from their husbands, officers and friends by 52.4%, pregnant women had a high intention of conducting an HIV test test of 53.2%. There is a significant relationship: attitude towards the intention of pregnant women to test for HIV and support towards the intention of pregnant women to test for HIV, attitude towards breastfeeding decisions, and support towards breastfeeding decisions, HIV test intentions towards breastfeeding decisions in Balikpapan city. Pregnant women with HIV positive must be disciplined in eating ARV (Anti-Retro Viral) to give breast milk to their babies, health workers must provide counseling and counseling to pregnant women about exclusive breastfeeding or formula milk.